Understanding climatic-landscape-hydrological interactions at a Meso-scale to guide global change adaptation : a study in the Kaleya river catchment, Zambia - Van der Laan, Michael (University of Pretoria, 2023)
Thesis (PhD (Water Resource Management))--University of Pretoria, 2022.